Let All Know: Insights from a Digital Storytelling Facilitator Training in Uganda - Yan, Tingting; Lang, Michael; Kyomuhangi, Teddy; Naggayi, Barbara; Kabakyenga, Jerome; Wasswa, William; Ashaba, Scholastic; Neema, Clementia Murembe; Tumuhimbise, Manasseh; Mutatina, Robens; Natumanya, Deborah; Brenner, Jennifer L. (Global Health Action, 2021)
Digital storytelling (DST) is a participatory, arts-based methodology that facilitates the creation of short films called digital stories. Both the DST process and resulting digital stories can be used for education, research, advocacy, and therapeutic purposes in public health. DST is widely used in Europe and North America, and becoming increasingly common in Africa. In East Africa, there is currently limited in-country DST facilitation capacity, which restricts the scope of use. Through a Ugandan-Canadian partnership, six Ugandan faculty and staff from Mbarara University of Science and Technology participated in a pilot DST facilitation training workshop to enhance Ugandan DST capacity.
Keywords: Digital storytelling; DST; Uganda; health promotion; participatory action research; health communicatio